The push-and-pull mechanism to scavenge redox-active transition metals: a novel concept in myocardial protection - Karck, Matthias; Tanaka, Satonori; Berenshtein, Eduard; Sturm, Christian Andreas; Haverich, Axel; Chevion, Mordechai (The journal of thoracic and cardiovascular surgery, 2001)
Objective: Traces of redox-active transition metals such as iron and copper play an important role in free radical formation during postischemic reperfusion of the heart. Two studies were conducted to assess the efficacy of the complexes of desferrioxamine with zinc or gallium to prevent this aspect of reperfusion injury. Methods: In study I, isolated working rat hearts (n = 96) were subjected to 2 hours of hypothermic arrest at 10°C induced by use of St Thomas' Hospital cardioplegic solution II supplemented with desferrioxamine, zinc-histidinate, zinc-desferrioxamine, gallium-nitrate, or gallium-desferrioxamine. In study II, isolated nonworking rat hearts (n = 23) were subjected to normothermic regional (10 minutes) or global (35 minutes) unprotected ischemia. In this study, the perfusate was supplemented with gallium-desferrioxamine during preischemic and postischemic periods. Results: In study I, the addition of desferrioxamine, zinc-histidinate, or gallium-nitrate to St Thomas' Hospital solution II improved postischemic aortic flow recovery. When the binary complexes zinc-desferrioxamine or gallium-desferrioxamine were added, however, functional recovery was further enhanced significantly. In study II, high-performance liquid chromatography analyses of tissue from postischemic hearts exposed to unsupplemented perfusate revealed a marked increase of malondialdehydes. In hearts perfused with perfusate supplemented with gallium-desferrioxamine, however, tissue malondialdehyde concentrations were significantly smaller, indicating reduced free radical formation. Conclusions: The data suggest synergistic protection by the complexes of the iron chelator desferrioxamine with zinc or gallium. The single components neutralize transition metals by 2 different but complementary push-and-pull mechanisms, thereby leading to an inhibition of metal-mediated site-specific free radical formation and improvement of postischemic cardiac function. (J Thorac Cardiovasc Surg 2001;121:1169-78)
Gesehen am 25.01.2022